2019
DOI: 10.1111/jhn.12696
|View full text |Cite
|
Sign up to set email alerts
|

Association between soft drink, fruit juice consumption and obesity in Eastern Europe: cross‐sectional and longitudinal analysis of the HAPIEE study

Abstract: Background Fruit juice and soft drink consumption have been shown to be related to obesity. However, this relationship has not been explored in Eastern Europe. The present study aimed to assess the cross‐sectional and longitudinal relationships between fruit juice, soft drink consumption and body mass index ( BMI ) in Eastern European cohorts. Methods Data from the Health, Alcohol and Psychosocial factors in Eastern Europe population‐based pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 42 publications
2
31
2
2
Order By: Relevance
“…The effect of dairy products on the absorption of fat (Jandacek, 1991), appetite, and metabolic activity of the gut microbiota (Marette & Picard‐Deland, 2014; Moreno, Bel‐Serrat, Santaliestra‐Pasías, & Bueno, 2015) is one of the underlying mechanisms affecting weight loss (Green, Stevenson, & Rumbold, 2017). Moreover, the literature showed that the prudent dietary pattern was inversely associated with unhealthy constituents such as snack and fast foods (Heald, 1992), soft drinks (Garduño‐Alanís et al, 2019; Katzmarzyk et al, 2016), and refined grains (Liu et al, 2003) that increased the odds of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of dairy products on the absorption of fat (Jandacek, 1991), appetite, and metabolic activity of the gut microbiota (Marette & Picard‐Deland, 2014; Moreno, Bel‐Serrat, Santaliestra‐Pasías, & Bueno, 2015) is one of the underlying mechanisms affecting weight loss (Green, Stevenson, & Rumbold, 2017). Moreover, the literature showed that the prudent dietary pattern was inversely associated with unhealthy constituents such as snack and fast foods (Heald, 1992), soft drinks (Garduño‐Alanís et al, 2019; Katzmarzyk et al, 2016), and refined grains (Liu et al, 2003) that increased the odds of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In Iranian eating habits, pickles, such as traditional appetizers, can be related to higher energy intake (Rouhani, Agh, & Azadbakht, 2018). In addition, soft drinks increase the odds of obesity, since they are full of sugar (Garduño‐Alanís et al, 2019; Katzmarzyk et al, 2016) and produce a lower sense of satiety (Pan & Hu, 2011). Refined grains, as the main portion of grains consumed by Iranian population (Bahadoran, Mirmiran, Delshad, & Azizi, 2014), are less nutrient‐dense, and have lower fiber (McKeown et al, 2010), so they increase odds of obesity (Liu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, in particular, increased availability of highly processed fast food (Zobel et al, 2016) and increased consumption of high-energy soft drinks are suggested to have importantly contributed to the obesity epidemic (Basu et al, 2013). There are convincing epidemiological data showing that soft drink consumption is associated with higher BMI (Garduño-Alanís et al, 2019) and increased weight gain in both children and adults (Luger et al, 2017;Malik et al, 2013). Physiologically, the association between soft-drink consumption and increased energy intake is expected, since high-energy drinks have only a weak satiety response (Maersk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The link between sugar-sweetened beverages (SSBs) and obesity and the broader impact of SSBs on health have been well-documented [1][2][3][4][5][6][7][8][9][10]. Taxes on SSBs are increasingly being recognised as an effective measure to reduce obesity and prevent non-communicable diseases (NCDs) [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%